2023
DOI: 10.1017/s0033291723000995
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use as a potential mediator between childhood adversity and first-episode psychosis: results from the EU-GEI case–control study

Abstract: Background Childhood adversity and cannabis use are considered independent risk factors for psychosis, but whether different patterns of cannabis use may be acting as mediator between adversity and psychotic disorders has not yet been explored. The aim of this study is to examine whether cannabis use mediates the relationship between childhood adversity and psychosis. Methods Data were utilised on 881 first-episode psychosis patients and 1231 controls from the European network of nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…IPT is associated with risk of addictive behaviours ( Konkolÿ Thege et al., 2017 ), including alcohol ( Berenz et al., 2016 ; Shin et al., 2009 ; Thompson et al., 2008 ), tobacco ( Kuzminskaite et al., 2021 ; Shin, 2021 ), cannabis abuse ( Aas et al., 2014 ; Chu, 2012 ), and substance poly-abuse ( Hedtke et al., 2008 ; Schimmenti et al., 2022 ). These findings are observed in both general population ( Hicks et al., 2022 ) and clinical samples ( Trotta et al., 2023 ; Aas et al., 2014 ). Yet, the interplay between IPT, substance use, and mental health symptoms is still understudied.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…IPT is associated with risk of addictive behaviours ( Konkolÿ Thege et al., 2017 ), including alcohol ( Berenz et al., 2016 ; Shin et al., 2009 ; Thompson et al., 2008 ), tobacco ( Kuzminskaite et al., 2021 ; Shin, 2021 ), cannabis abuse ( Aas et al., 2014 ; Chu, 2012 ), and substance poly-abuse ( Hedtke et al., 2008 ; Schimmenti et al., 2022 ). These findings are observed in both general population ( Hicks et al., 2022 ) and clinical samples ( Trotta et al., 2023 ; Aas et al., 2014 ). Yet, the interplay between IPT, substance use, and mental health symptoms is still understudied.…”
Section: Introductionmentioning
confidence: 55%
“…For example, cannabis use may reduce depressive symptoms but increase psychotic symptoms in vulnerable individuals ( Di Forti et al., 2019 ; Feingold and Weinstein, 2021 ; Quattrone et al., 2019 ). Recent studies showed that the use of cannabis mediates the link between some traumatic events and the risk of psychosis ( Frydecka et al., 2020 ; Trotta et al., 2023 ) which suggest that for some individuals the impact of IPT on severe mental health symptoms is via cannabis use ( Frydecka et al., 2020 ; Trotta et al., 2023 ). Furthermore, the recent legalization of cannabis across western countries ( Di Forti, 2020 ) highlights the pivotal importance to understand the impact of substance use on mental health among vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%